Analisis Pengelolaan Retribusi Pelayanan Persampahan Di Kota Semarang: Sebuah Kajian Interdisipliner Untuk Meningkatkan Kinerja Dan Kualitas Pelayanan - Aris Toening Winarni; Arul Asyidikri (Universitas 17 Agustus 1945 Semarang, 2024)
The management of waste retribution in Semarang City has encountered problems with low target achievement of retribution. This can hamper the government's efforts in providing optimal waste management services. This study aims to describe and analyze the management of waste retribution as a reference to plan for increasing the target and realization achievement of waste retribution in Semarang City. This research uses a qualitative approach with a phenomenological method involving in-depth interviews, data reduction, inductive analysis, data validity, and drawing conclusions, using an administrative theory approach with the principles of planning, organizing, directing, and controlling as a framework for thinking about waste retribution management. The results show that the planning process is not yet optimal, the organization is not yet effective, the direction of fund use is quite effective, and the control is strict but financial reporting needs improvement in transparency and accountability. The suggestions given include increasing socialization and education, forming a special unit to manage retribution, evaluating and adjusting tariffs, increasing transparency in financial reporting, and involving stakeholders in monitoring and evaluation.